Immunological properties of protocatechuate 3, 4-dioxygenase isofunctional enzymes. - Hou, C T (1976)
Antiserum prepared against protocatechuate 3, 4-dioxygenase from Pseudomonas aeruginosa forms precipitin bands without spurs with isofunctional enzymes from different strains of the fluorescent pseudomonads on immunodiffusion plates. Catalytic activity of the isofunctional enzymes was inhibited by an immunoglobulin fraction prepared against the enzyme from organisms of the same genus and not from different genera.